Building construction handbook - Chudley, R.; Greeno, Roger (2014)
"The Building Construction Handbook is THE authoritative reference for all construction students and professionals. Its detailed drawings clearly illustrate the construction of building elements, and have been an invaluable guide for builders since 1988. The principles and processes of construction are explained with the concepts of design included where appropriate. Extensive coverage of building construction practice, techniques, and regulations representing both traditional procedures and modern developments are included to provide the most comprehensive and easy to understand guide to building construction. This new edition has been updated to reflect recent changes to the building regulations, as well as new material on the latest technologies used in domestic construction."--back cover.
General -- Site works -- Builders plant -- Substructure -- Superstructure -- Internal construction and finishes -- Domestic services.
Previous edition: 2013.
Includes index.
Keywords: Building -- Handbooks, manuals, etc; Construction industry -- Handbooks, manuals, etc